Manajemen Diri Pasien Diabetes Mellitus Tipe 2 terhadap Kadar Gula Darah: Eksperimental Study - Trina Kurniawati; Rita Dwi Hartanti; Eka Budiarto (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective: This study to determine the effect of self-management of Type 2 DM patients on blood sugar levels.Methods: The method of this study used a quantitative This study used a quasi-experimental design with pre post test without control group. A total of 23 patients with Type 2 DM become as respondents with a sampling technique used purposive sampling. The inclusion criteria applied to respondents included age more than 35 years, received a diagnosis of Type 2 DM from a doctor since at least 2 years ago, is currently active in treatment, and is willing to participate in the full course of the study. The measuring instrument used is a checklist sheet containing data on blood sugar levels before and after self-management of Type 2 DM patients. Pre and post measurements were given 1 month. Data were analyzed using McNemar Test.Results: There is an effect of self-management of Type 2 DM patients on changes in blood sugar levels (p value 0.008).Conclusion: Self-management of Type 2 DM patients has been shown to improve DM control, especially in controlling blood sugar in the body. Self-management carried out by patients with Type 2 DM in this study was seen to be optimal in aspects of diet regulation, physical activity regulation, and taking medication regularly.